IL-6-mediated cross-talk between human preadipocytes and ductal carcinoma in situ in breast cancer progression - Kim, Hoe Suk (J Exp Clin Cancer Res, 2018)
BACKGROUND: The function of preadipocytes in the progression of early stage breast cancer has not been fully elucidated at the molecular level. To delineate the role of preadipocytes in breast cancer progression, we investigated the cross-talk between human breast ductal carcinoma in situ (DCIS) cells and preadipocytes with both an in vitro culture and xenograft tumor model. METHODS: GFP or RFP was transduced into human DCIS cell line MCF10DCIS.com cells or preadipocytes using lentivirus. Cell sorter was used to separate pure, viable populations of GFP- or RFP-transduced cells. Cell viability and proliferation was assessed by crystal violet assays and cell migration and invasion capability was assayed by the transwell strategy. Gene and protein levels were measured by western blot, RT-PCR and immunostaining. Adipokines and cytokines were quantified using ELISA. Human tumor xenografts in a nude mice model were used. Ultrasound imaging of tumors was performed to evaluate the therapeutic potential of a IL-6 neutralizing antibody. RESULTS: In the co-culture system with the MCF10DCIS.com and preadipocytes, MCF10DCIS.com proliferation, migration and invasion were enhanced by preadipocytes. Preadipocytes exhibited in an increased IL-6 secretion and cancer-associated fibroblast markers expression, FSP1 and α-SMC in co-culture with MCF10DCIS.com or in MCF10DCIS.com conditioned media, whereas the adipocyte differentiation capacity was suppressed by co-culture with MCF10DCIS.com. A neutralizing antibody of IL-6 or IL-6R suppressed the promotion of MCF10DCIS.com proliferation and migration by co-culture with preadipocytes. In the xenograft tumor model, the tumor growth of MCF10DCIS.com was enhanced by the co-injection of preadipocytes, and the administration of IL-6 neutralizing antibodies resulted in potent effects on tumor inhibition. CONCLUSIONS: Our findings suggest that IL-6-mediated cross-talk between preadipocytes and breast DCIS cells can promote the progression of early stage breast cancer. Therefore, blocking IL-6 signaling might be a potential therapeutic strategy for breast DCIS characterized by pathological IL-6 overproduction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-018-0867-3) contains supplementary material, which is available to authorized users.